Prognostic accuracy of Whole Lung Perfusion Blood Volume as a predictor of 28-day Mortality in Acute Pulmonary Thromboembolism – A prospective study - N Krishna Reddy; Subathra Adithan; Shubhamoy Gantait; Venkateswaran Ramanathan; Manju Rajaram (Lung India)
Background: The estimated incidence of pulmonary embolism (PE) is around 60–70 cases per 100,000 people annually. The overall mortality rate for massive PE is substantial, ranging from 18% to 65%. We can utilise changes in lung perfusion to stratify patients with PE acutely based on risk, highlighting its diagnostic and prognostic value. Objectives: To calculate the whole-lung perfused blood volume (PBV) and right-to-left ventricular diameter ratio from dual-energy computed tomography thorax in patients with acute PE and find its association with 28-day all-cause mortality. Methods: This was a prospective diagnostic accuracy study at the Jawaharlal Institute of Post-Graduate Medical Education and Research. We included suspected acute PE patients. A dual-energy chest CT was performed on all these patients, and iodine maps were generated using the Syngo dual-energy workstation. Whole-lung PBVs were then calculated. Patients were followed up for 28 days, and all-cause mortality data were collected. The prognostic accuracy of PBVs in predicting mortality among acute PE patients was analysed using the ROC curve using SPSS version 19.0. Results: The area under the curve (AUC) was 0.696, indicating a moderate discriminatory power in distinguishing between patients who experienced mortality and those who did not. An empirical cut-off value of 0.945 corresponds to a sensitivity of 63.2% and a specificity of 67.6%. Conclusion: The prognostic accuracy of total perfused lung volume/total lung volume revealed a moderate discriminatory power, indicating 70% accuracy in predicting 28-day mortality based on standardised total PBVs.